Utilization of Telegram application As an Information Media Face Mask Detection Result - Muhammad Furqan Rasyid; Andi Asvin Maherssatillah Suradi; Arham Arifin; Muhammad Rizal; Mushaf Mushaf (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
To know the results of the face mask detection system, one must be near a computer. This problem makes it difficult to reprimand and provide face masks to violators. One of the ways to prevent the spread of the virus is to wear a mask. This study focuses on making a face mask detection system connected to a cellular device. This study aims to make obtaining information more effortless, and monitoring officers can find out from a smartphone. As a medium of communication, we use the telegram application. Smartphone users widely use this application compared to existing messaging media applications. This study uses the YoloV4 algorithm to detect face mask and JSON to send information to the telegram application. The test consists of two stages, the first stage is to determine the accuracy of the face mask detection system and the second stage is to determine the average time required until the information is sent. The two tests performed obtained 97.57% and 0.255 seconds, respectively. The test results show that the system created can solve the existing problems. The researcher can do further research by increasing the number of datasets to increase the accuracy of face mask detection.Keywords: Face Mask Detection, JSON, Telegram Application, YoloV4 Algorithm.